Impact of coating layers in rotary cement kilns: Numerical investigation with a blocked-off region approach for radiation and momentum. (1st March 2020) - Wirtz, S.; Pieper, C.; Buss, F.; Schiemann, M.; Schaefer, S.; Scherer, V.
Graphical abstract: Highlights: CFD-simulations of rotary cement kilns considering coating layers. Iterative determination of coating thickness based on kiln shell temperature profiles. Blocked-off region approach successfully used to describe coating layers in the kiln. Coating layers found to have a significant impact on process conditions. Abstract: In this study CFD simulations of an industrial scale rotary kiln for cement clinker production are conducted. A solid layer of agglomerated clinker material, which adheres to the kiln wall and forms a stable coating of variable thickness during kiln operation, is considered in the simulations of the furnace. During operation of the kiln the thickness of the coating layer is unknown, but the routinely measured temperature profile along the kiln shell is an indicator for the local layer thickness. Therefore, a first estimate of the initially unknown thickness of the coating layer is calculated by a one-dimensional heat transfer model, based on the temperature profile along the kiln shell, and introduced into the CFD simulations. As the process conditions within the furnace and, thus, the heat transfer to the kiln wall and the resulting coating thickness change over time, an adaptive modelling approach is required to describe the solid coating region in the CFD simulations. A method to represent the geometry of the coating layer as a blocked-off region for momentum is presented and extended for radiation. The results are compared to the conventional approach where the coating layer is represented by a highly resolved CFD mesh following the wall contour. Two generic temperature profiles of the kiln shell are assumed and used to simulate the corresponding coating profile in the furnace. The effect on the process conditions within the kiln are assessed and compared to a reference case without coating regions. Results show that the blocked-off approach employed is suitable to model the additional solid boundary profile in the furnace. The coating regions are found to have a significant impact on the process conditions within the kiln, especially if the coating layers are located towards the burner end of the kiln.